Helically aligned fused carbon hollow nanospheres with chiral discrimination ability. Issue 10 (15th February 2022) - Maruyama, Jun; Maruyama, Shohei; Kashiwagi, Yukiyasu; Watanabe, Mitsuru; Shinagawa, Tsutomu; Nagaoka, Toru; Tamai, Toshiyuki; Ryu, Naoya; Matsuo, Koichi; Ohwada, Mao; Chida, Koki; Yoshii, Takeharu; et al.
Abstract : Helically aligned fused carbon hollow nanospheres on multiwalled carbon nanotubes are formed as a new form of helical structure with optical activity and chiral spaces showing chiral discrimination ability without the attachment of chiral compounds. Abstract : While the functions of carbon materials with precisely controlled nanostructures have been reported in many studies, their chiral discriminating abilities have not been reported yet. Herein, chiral discrimination is achieved using helical carbon materials devoid of chiral attachments. A Fe3 O4 nanoparticle template with ethyl cellulose (carbon source) is self-assembled on dispersed multiwalled carbon nanotubes (MWCNTs) fixed in a lamellar structure, with helical nanoparticle alignment induced by the addition of a binaphthyl derivative. Carbonization followed by template removal produces helically aligned fused carbon hollow nanospheres (CHNSs) with no chiral molecules left. Helicity is confirmed using vacuum-ultraviolet circular dichroism spectroscopy. Chiral discrimination, as revealed by the electrochemical reactions of binaphthol and a chiral ferrocene derivative in aqueous and nonaqueous electrolytes, respectively, is attributable to the chiral space formed between the CHNS and MWCNT surfaces.